Taking stock of expatriates’ career success after international assignments: a review and future research agenda - Mello, Rodrigo; Suutari, Vesa; Dickmann, Michael (Elsevier, 2022)
This systematic literature review explores studies addressing the objective career success and subjective career success of company-assigned and self-initiated expatriates after their long-term international assignments. Expatriate work is defined as high-density work that affects employee learning and career trajectories. We develop a holistic expatriate career success framework exploring the following questions: 1) What individual career impact results from international assignments? 2) What are the antecedents of such career success? and 3) What are the outcomes of assignees’ career success? A previously neglected range of theoretical perspectives, antecedents, and outcomes of expatriate career success is identified. Subsequently, a threefold contribution is made. First, we extend the conceptualization of international work density to unveil the differences between general and global career concepts. Second, we identify promising theories that have not been utilized in expatriation research, emphasizing context-related and learning theories that chime with the specific nature of global careers. Lastly, we suggest an extensive future research agenda.
Keywords: Expatriation; Assigned Expatriates; Self-initiated Expatriates; Repatriation; Re-expatriation; Career Success